1982
DOI: 10.1002/bbpc.19820860718
|View full text |Cite
|
Sign up to set email alerts
|

Micellisation Processes in Concentrated Sodium Deoxycholate Solutions – Effect of Different Counterions

Abstract: The effect of different electrolytes (NaBr, CsBr, Bu4NBr) on the micellisation processes of Sodium Deoxycholate solutions has been studied by means of various experimental techniques (densimetric, viscometric and microwave dielectric measurements) in the concentration range above the first critical micelle concentration. The size and shape of the secondary micelles are estimated and the role of the interfacial water in these aggregation processes discussed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

1985
1985
2016
2016

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 15 publications
0
6
0
Order By: Relevance
“…In the presence of these sodium salts of fatty acids, cmc values of NaDC were, however, not reported [2]. Sesta et al [3] measured density, viscosity, and microwave dielectric constant of NaDC in the postmicellar concentration region in the presence of sodium bromide, cesium bromide, and tetrabutylammonium bromide, and reported only the effect of these salts on the second cmc of NaDC. Jana and Moulik [4] reported the interaction of dodecyl sulfate anion with anions of different bile salts based on surface tension, conductance, and calorimetric measurements.…”
Section: Introductionmentioning
confidence: 94%
See 1 more Smart Citation
“…In the presence of these sodium salts of fatty acids, cmc values of NaDC were, however, not reported [2]. Sesta et al [3] measured density, viscosity, and microwave dielectric constant of NaDC in the postmicellar concentration region in the presence of sodium bromide, cesium bromide, and tetrabutylammonium bromide, and reported only the effect of these salts on the second cmc of NaDC. Jana and Moulik [4] reported the interaction of dodecyl sulfate anion with anions of different bile salts based on surface tension, conductance, and calorimetric measurements.…”
Section: Introductionmentioning
confidence: 94%
“…Nevertheless, coions from the added electrolyte, if they have sufficient hydrophobicity in their structure, may also influence the adsorption and aggregation of ionic surfactants. In the case of bile salts, the effect of NaCl on their micellization has been studied extensively and regarding the effect of other electrolytes we could find only three reports [2][3][4]. Shilnikov et al [2] made density, ultrasound velocity, and NMR studies of sodium deoxycholate (NaDC) in the presence of sodium salts of homologous fatty acids (C 3 -C 18 ), which indicated that carboxylate ions of chain length 6C 9 do not interact with deoxycholate micelles, while those of chain length >C 9 formed mixed micelles with NaDC.…”
Section: Introductionmentioning
confidence: 98%
“…Micelle growth in BS is documented by a lot of experimental evidence, based on viscosity [60-64], DLS and QELS [65][66][67][68][69], NMR self-diffusion [70,71] and so forth [72][73][74]. Such data point out to the existence of an almost continuous association process, driven by surfactant uptake onto micelles and/or by the screening of the electrostatic repulsions occurring between them.…”
Section: Supra-molecular Associationmentioning
confidence: 99%
“…We estimated it by the densities reported in literature, namely, 1.3 for STDC [11,12] and 1.1 for DDAB [13]. In Fig.…”
Section: Nmr Diffusometrymentioning
confidence: 99%
“…with D w0 the self-diffusion coefficient of free water, here approximated by the one of pure water, and ˚surf the surfactant volume fraction. We estimated it by the densities reported in literature, namely, 1.3 for STDC [11,12] and 1.1 for DDAB [13]. In Fig.…”
Section: Nmr Diffusometrymentioning
confidence: 99%